Psychometric Properties of the Indonesian Version of Religious Orientation Scale in Muslim Adolescents Sample - Rahmah, Muthia; Maulina, Dewi; Latifa, Rena; Ein, Indy Hurun (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2025)
This study aimed to validate the Indonesian version of the Religious Orientation Scale (ROS-I), an adaptation of Allport and Ross’s (1967) measure of intrinsic and extrinsic religious orientation, using the Rasch model analysis. ROS-I, which consists of two subscales: Intrinsic Religious Orientation (IRO) and Extrinsic Religious Orientation (ERO) was tested to 410 Muslim adolescents from the Greater Jakarta area using online questionnaire. The psychometric evaluation showed that the ROS-I had good index of person and item separation, unidimensional construct, local independence, good item fit index, and good distributions for its rating scales. Therefore, the ROS-I has generally proven to be a valid and reliable tool for evaluating two aspects of religious orientation in Indonesian Muslim adolescents. However, this study restriction to Muslim adolescents’ population may limit its generalizability that calls for broader and more diverse population for future research. Nevertheless, the validated ROS-I offers a useful assessment of religious orientation in Indonesia and similar cultural settings.